PKM IMPLEMENTASI DIGITAL LITERACY DALAM PEMBELAJARAN BAHASA INGGRIS PADA SISWA SMK DI KABUPATEN SEMARANG - Endang Susilowati; Ari Siswati; Hardiany, Dewi (Universitas Ngudi Waluyo, 2024)
The Implementation of Digital Literacy in English Language Learning for Students of SMK Muhammadiyah Ungaran Semarang Regency is carried out to increase students' interest in learning, especially in English lessons by applying digital literacy, especially Kahoot. The background of this activity is to overcome some problems in English learning, for example: lack of references and students' low interest in learning English. Learning methods that are less developed and carried out rigidly can cause boredom for students. Generating interest in learning English is one of the tasks and challenges for English teachers. The implementation of the activity begins with socialization to the students of Universitas Ngudi Waluyo who are involved in this activity, followed by coordination with the target school regarding the implementation schedule. It ends with reporting the results of activities after the implementation of the program is complete. This program provides benefits not only for the students but also for the teachers at SMK Muhammadiyah Ungaran. The English teachers get new insight for teaching method by using digital application. This method is proven interested for the students and help them to understand English more easily Keywords: Digital Literacy, English language learning